Current practices in the veterinary use of antibiotics in poultry laying hens in Friguiagbé (Guinea) - SOROMOU, Lanan Wassy; LENO, Pierre Faya; KAMANO, Alhassane; SOUARE, Mamadou Lamarana; CAMARA, Almamy Ousmane Deen; CAMARA, Karifa (Journal of Drug Delivery and Therapeutics, 2024)
The use of antibiotic molecules on poultry farms, while justified by their efficacy, must be carried out rationally, as their uncontrolled use modifies the ecology of bacteria and thus contributes to the selection of multi-resistant bacteria. The aim of this study was to carry out a descriptive survey of antibiotic use on laying hen farms in the sub-prefecture of Friguiagbé (Kindia). To achieve this, surveys were carried out among veterinary service managers, poultry farmers and sales outlets. At the end of our work, we identified the existence of two (2) veterinary pharmaceutical supply establishments. Establishments selling veterinary medicines revealed that Tetracycline is the most widely marketed antibiotic family. The most widely used antibiotic molecules are Tetracolivit and Oxytetracycline (26%); Neoxyvital (13%); Alfaceryl and Panteryl (8%); Limoxin (5%); Enrofloxacin, TTS, Colisol and Amoxillin (3%), which are used either for preventive or curative purposes. Keywords : Antibiotic molecules, poultry farming, laying hens, Guinea